Large borehole with multi-lateral branches: A novel solution for exploitation of clayey silt hydrate - Yan-long Li; Yi-zhao Wan; Qiang Chen; Jia-xin Sun; Neng-you Wu; Gao-wei Hu; Fu-long Ning; Pei-xiao Mao (China Geology, 2019)
ABSTRACT: ontact area are two main ways to raise the productivity of hydrate. An exploitation technique based on large borehole with multi-lateral branches (LB & MB) was proposed in this paper. This technique is mainly intended for the clayey silt hydrate reservoir in the South China Sea, and its main purpose is to alleviate the sand output from formation for maintaining the stability of the reservoir and to greatly increase the gas productivity of the reservoir. In this paper, the following aspects were mainly expounded: definition of the basic geometric parameters for layout of multi-lateral branches in clayey silt hydrate reservoir, simulation of the stimulation effect of a typical well profile with two branches, and prediction and simulation of the reservoir failure risk in a well profile with eight branches. The results show that the LB & MB effectively improves the flow field in the formation, raises the productivity of the reservoir and may also help to decrease the produced water-gas ratio (WGR). When the lateral branches spacing is too small, the failure zones around adjacent lateral branches overlap each other, possibly causing reservoir failure in a larger range. Therefore, the geometric parameters of multi-lateral branches depend on the dual control of the productivity and geotechnical risk factor of reservoir. Further study is being carried out, so as to obtain the optimal combination of parameters of multi-lateral branches.